2020
DOI: 10.1039/d0cc00128g
|View full text |Cite
|
Sign up to set email alerts
|

The affinity of RSK for cylitol analogues of SL0101 is critically dependent on the B-ring C-4′-hydroxy

Abstract: The de novo asymmetric synthesis of carbohydrates for the SAR-study of the anticancer natural product, SL0101.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Specifically the C-4 ketone in Pd-πallyl B imparts the requisite electrophilicity to react with unactivated alcohols. [27][28][29][30][31][32][33] Thus, we were pleasantly surprised with the overall facility of this vinylogous pyranone palladium(0)-glycosylation (via Pd-π-allyl A), as it compared well to the parent variant (via Pd-π-allyl B) in terms of reactivity with unactivated alcohols, and regio-and stereoselectivity.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically the C-4 ketone in Pd-πallyl B imparts the requisite electrophilicity to react with unactivated alcohols. [27][28][29][30][31][32][33] Thus, we were pleasantly surprised with the overall facility of this vinylogous pyranone palladium(0)-glycosylation (via Pd-π-allyl A), as it compared well to the parent variant (via Pd-π-allyl B) in terms of reactivity with unactivated alcohols, and regio-and stereoselectivity.…”
Section: Resultsmentioning
confidence: 99%
“…Structure-activity-relationship (SAR) studies using SL0101 as the lead compound were used to identify the analogue C5″ n -propyl SL0101 ( Figure 5A ) ( Smith et al, 2006 ; Smith et al, 2007 ; Hilinski et al, 2012 ; Mrozowski et al, 2012 ; Mrozowski et al, 2014 ; Li et al, 2015 ; Ludwik et al, 2016 ; Li et al, 2017 ; Li et al 2020a ; Li et al 2020b ; Wright et al, 2021 ) ( Supplementary Tables S2, S3 ). This analogue has an improved potency of two-fold in RSK2 in vitro kinase assays (IC 50 –392 nM vs. 183 nM (10 μM ATP)) and five-fold in cell-based assays compared to SL0101 (IC 50 50 μM vs. 8 μM in an MCF-7 cell line).…”
Section: Rsk Inhibitorsmentioning
confidence: 99%
“…2, 165.4, 165.0, 104.7, 95.2, 33.1. 1-(2,4-Bis(benzyloxy)-6-hydroxyphenyl)ethan-1-one (7). 23 To a solution of triol 13 (28 g, 0.17 mol) in 100 mL dimethylformamide (DMF), K 2 CO 3 (97.2 g, 0.7 mol) was added portionwise followed by the dropwise addition of benzyl bromide (84 mL, 0.7 mol) over a 1 h period at 0 °C.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…As part of an effort to find selective inhibitors of the p90 ribosomal s6 kinases (RSKs), the glycosylated kaempfer-3-ol natural product, SL0101 ( A ), was identified as a relatively selective inhibitor for RSK1/2 (Ki ∼ 1 μm). , In a combination of molecular modeling and structure–activity relationship studies (Figure ), , we identified carbohydrate ( 1a – e ) and cyclitol analogues ( 2a – e ) of SL0101 ( A ) with improved kinase and cancer cell inhibitory activity. , These activities involved on the synthesis of stereoisomers and analogues with substitution at the aglycone (e.g., C-4′ of the kaempfer-3-ol) and carbohydrate (e.g., C-6” of the rhamnose ring) portions of the natural product. These efforts focused on the synthesis of nonhydrolyzable alternatives to the pyranose (e.g., carbasugar) and C -3′/4′ acetate groups (e.g., amide and carbamate substitutions at C -3′ and/or C -4′) .…”
mentioning
confidence: 99%